Location based social media content: a conceptual paper on travellers purchase decisions - Rehman Khan, Haseeb ur; Chen Kim, Lim; Lam Tan, Kian; Rehman Khan, Mustafa (Management Research Journal, 2019)
The aim of this paper is to conceptualize the significance of location based user generated content in creating superior value to aid travellers in their decision making regarding traveling products and services. A comprehensive review of latest conceptual and empirical literature was grounded to develop the propositions. Millennial generation of Malaysia shall be taken as a social lab for examining the propositions, and to report the empirical findings. The finding of this study provides a basis for developing a model to obtain the significance of location base user generated content on travel decisions. This study could be of practical value for organizations and highlighted the importance of participatory user generated content as well as significant for travellers who want to improve on-travel decisions accuracy. This study suggested a special focus on millennials in Malaysia since they are considered as a potential cluster of markets. This paper makes a significant contribution by developing a conceptual framework to improve travel decision accuracy through location base user generated content among millennials in Malaysia.